Development of Village Potential into a Tourism Village in Nglegi Gunungkidul Village - Purwoko, Yitno; Wigati, Erna; Pradapa, Sri Yulianto Fajar; Noviastuti, Nina; Hakim, M Fathurrahman Nurul; Kustini, Henny (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
This article aims to discover the potential of Nglegi Village and the development that can be carried out regarding the facilities it has to become a tourist village. The method used in this research is a qualitative method by observing and interviewing stakeholders, community leaders and Pokdarwis managers to know the potential and facilities owned by Nglegi Village. The result of this research is to develop the possibilities that exist in Nglegi Village by exploring the potential and completing facilities that have not yet been owned to be able to develop Nglegi Village into a tourist village by strengthening human resources equipped with training to make superior human resources and competent who can support Nglegi Village to become a pilot Tourism Village.